Telocytes of the male reproductive system: dynamic tissue organizers - Sanches, Bruno D. A.; Rocha, Lara C.; Neto, J. Pimentel; Beguelini, Mateus Rodrigues; Ciena, Adriano P.; Carvalho, Hernandes F. (Frontiers in Cell and Developmental Biology, 2024)
Telocytes are CD34+ interstitial cells that have long cytoplasmic projections (called telopodes), and have been detected in several organs, including those of the male reproductive system. In this brief review we evaluate the role of telocytes in tissue organization of the different organs of the male reproductive system in which these cells were studied. In general terms, telocytes act in the tissue organization through networks of telopodes that separate the epithelia from the stroma, as well as dividing the stroma into different compartments. In addition to this contribution to the structural integrity, there is